Estimating NHL scoring rates - Buttrey, S. E.; Washburn, A. R.; Price, W. L. (Journal of Quantitative Analysis in Sports, 2011)
We propose a model to estimate the rates at which NHL teams score and yield goals. In the model, goals occur as if from a Poisson process whose rate depends on the two teams playing, the home-ice advantage, and the manpower (power-play, short-handed) situation. Data on all the games from the 2008-2009 season was downloaded and processed into a form suitable for the analysis. The model seems to perform adequately in prediction and should be useful for handicapping and for informing the decision as to when to pull the goalie.